KONSTRUKSI PEMBENTUKAN KARAKTER PADA KELUARGA SUKHINAH DI GRAHA PASEK BANJAR KAJA KELURAHAN SESETAN KECAMATAN DENPASAR SELATAN KOTA DENPASAR - Ni Made Surawati; Ida Ayu Putu Sari; A.A Ketut Raka (WIDYANATYA, 2021)
The family is the first and foremost place of education for children. However, due to the influence of globalization and modernization, the phenomenon of materialistic and consumerist lifestyles has emerged, so that true happiness is measured by material (artha). Such a lifestyle can certainly cause a shift in the meaning of the family, such as the rise of divorce rates, family disorganization, lack of parental attention to children, domestic violence, MBA, and degradation of the younger generation. It is feared that people's lives can cause the values â€‹â€‹of social wisdom, spiritual values, and the duties of parents in building character in children to be neglected. Related to that, there is a family phenomenon in the city of Denpasar, namely the Graha Pasek family which is thought to be able to educate good character in their sons, and is suspected of being able to maintain the value of harmony between other family members, so that researchers are interested in conducting a deeper study of "Construction of the Formation of Characters in the Sukhinah Family at Graha Pasek Banjar Kaja, South Denpasar District, Denpasar Cityâ€. This study is intended to answer problems that include the basis, form, and implications of the construction of character formation in the sukhinah family at Graha Pasek Banjar Kaja, Sesetan Village, South Denpasar District, Denpasar City. There are three theories used to dissect the problem, namely the Humanistic Theory proposed by Abraham Harold Maslow, Constructivism Theory by Jean Piaget, and Character Theory by Thomas Lickona. This research is a type of qualitative research, so the data is obtained through observation, interviews, and document studies. Based on the analysis and study of the data, the findings were obtained as a result of the study, including: (1) The basis for the construction of character formation in the sukhinah family at Graha Pasek Banjar Kaja, including: the Marriage Law and marriage according to Hinduism, the criteria for the sukhinah family, and the pattern of marriage. foster a Hindu perspective. (2) The form of character building construction for the Sukhinah family at Graha Pasek, namely: Implementation of the selection of the Sukhinah family at Graha Pasek, the character education model for the Sukhinah family (dharmika, subhiksa, mahatmya, kertasanta) accompanied by the principles of openness and sincerity (lascarya), and the process the construction of character building in the sukhinah family which includes the embodiment of the Hindu perspective parenting style, the transformation of values, and the practice of husband-wife swadharma (obligations). (3) The implications of the construction of